Aplicación de Google Earth y GPS en el muestreo aleatorio de viviendas en un estudio epidemiológico de Demodex canis en perros - Mendoza, Yasmin (2025)
Epidemiological studies in rural areas require effort due to the irregular geographic configuration. In Abancay (Peru), a study was conducted to evaluate the effectiveness of random sampling using Google Earth and GPS to determine the number of dogs per household and the factors associated with demodicosis in domestic dogs. In total, 200 households were analysed using Google Earth from 5950 m altitude and GPS to identify them. Skin samples were collected for laboratory analysis. The identification of households with Google Earth was 96% effective. Besides, 1.29 dogs were found per household. The etiologic agent of scabies was Demodex canis with a prevalence of 22.5% (95% CI, ±5.79). Crossbreed dogs from 1 to 6 years old, not bathed or deworming, and living in peripheral areas of the city were the most affected with prevalences between 12.5 and 18.5%. The parasite was distributed proportionally by sex and location of the doghouse. Of the variables analysed (age, sex, breed, frequency of deworming, frequency of bathing, arrangement of the doghouse and area of residence), only the frequency of bathing was significant in the increase in Demodex population (p<0.01), although its effect was dependent on its categories. Google Earth was very effective in random sampling in an area of irregular geography. One fifth of the dogs were affected with Demodex canis, and only the frequency of bathing was a relevant factor identified.